Pharmacogenetics and oral antithrombotic drugs. (April 2016) - Baker, William L; Johnson, Samuel G
Highlights: Warfarin dose requirements to achieve therapeutic anticoagulation are highly variable. Genetic variants in VKORC1 and CYP2C9 gene are associated with increased sensitivity to warfarin. Clinical trials evaluating incorporation of warfarin genotype into dosing algorithms have yielded mixed results. Research continues to determine the precise impact of genotype-guided warfarin therapy on patient outcomes. Polymorphisms of dabigatran metabolism may change plasma concentrations and alter bleeding risk. Abstract : Warfarin and other oral vitamin K antagonists (VKAs) have been the primary pharmacologic options with well-established efficacy data in high-risk patient populations. Warfarin dose requirements to achieve therapeutic anticoagulation are highly variable. This variability in response results in increased risk for adverse events, including thromboembolism and bleeding. Genetic variants in CYP2C9 and VKORC1 have been identified and shown to explain some of the variability in warfarin response. Prospective trials suggest that incorporation of genotype results in faster time to therapeutic range than without; however, whether these improvements result in improved clinical outcomes is unclear. The target-specific anticoagulants are alternatives to warfarin and do not require laboratory monitoring. Some pharmacogenetic variation in their clinical response may exist as well. Ongoing trials will provide a clearer picture of whether genotype-based warfarin dosing improves outcomes and may, therefore, subsequently be compared with the target-specific agents.